The Correlation Among LLS (Language Learning Strategies), Students' Reading Interest, and Students' Reading Comprehension - M Bambang Purwanto (Channing : Journal of English Language Education and Literature, 2021)
For Indonesian senior high school students, reading comprehension does not only extensively improve their knowledge in general but also their English achievement. The pieces of evidence show us that English assessments are mostly given in the form of reading text. Therefore, the ability to understand the information from the text is inevitability precious in our educational setting. the Indonesian students' reading comprehension achievement is still low because only 69% have the lowest level of reading. Students of SMA (Senior High School) still have the poor reading ability, it is shown by They can finish reading text but they can not answer some questions correctly based on the theme that they have already read. It means that they can not comprehend the text well. Based on the problems, the researcher wants to investigate the Correlation among LLS (Language Learning Strategies), Students' Reading, and Students' Reading Comprehension. Furthermore, the population of the research is the ninth students of SMPN 27 of Palembang consisting of 133 students, from the population, 60 students were represented as the sample which was taken through the probability sampling technique. The instrument to collect the data used questionnaires for LLS and Reading Interest therefore Reading Comprehension was taken by students' reading test. While analyzing the data, was used multiple correlation in SPSS 20 for Windows. The data analysis showed that the result of Ryx1x2 = 0.448 withR2 = 0.200 (or 20.0%) contributed of LLS and 80%. from linear regression analysis, it showed that regression between X1 and Y is FCount = 7.139 > Ftable(73) = 2.61, which means that linear and significant. Hopefully, it is suggested to provide with some useful lessons of LLS and reading interest that may help the readers improve the quality of their reading comprehension